Pembelajaran Pendidikan Agama Islam (PAI) berbasis Pembinaan Akhlak Peserta Didik di Madrasah Aliyah Al-Azhar Center Baturaja - Rahmawati Rahmawati; Danyi Riyani; Desi Oktarianti (Al-Munawwarah : Jurnal Pendidikan Islam, 2026)
This study aims to analyze the implementation of Islamic Religious Education (IRE) learning in fostering students' moral character at MA Al-Azhar Center Baturaja, describe the actual condition of students' morality, and identify the supporting and inhibiting factors affecting its implementation. This research employed a qualitative approach with a descriptive design. Data were collected through observation, in-depth interviews, and document analysis involving the principal, Islamic Religious Education teachers, and students. Data were analyzed using the interactive model consisting of data condensation, data display, and conclusion drawing, while data trustworthiness was ensured through source triangulation, technique triangulation, and member checking. The findings reveal that the implementation of IRE learning has been systematically carried out through the integration of classroom instruction, teacher role modeling, and religious habituation that collectively shape the school's religious culture. The students' moral character was generally categorized as good, as reflected in their religious attitudes, discipline, responsibility, and social awareness, although several behavioral issues still require continuous guidance. Supporting factors include the principal's leadership, teachers' professional competence, the school's religious culture, and structured habituation programs. Meanwhile, inhibiting factors involve limited parental supervision, peer environmental influences, and the uncontrolled use of digital media. The study concludes that successful moral character development requires strong collaboration among schools, families, and communities through strengthening religious culture and implementing Islamic Religious Education that emphasizes the internalization of Islamic values.